Pyridinediimine Iron Dicarbonyl Complexes with Pendant Lewis Bases and Lewis Acids Located in the Secondary Coordination Sphere. Issue 22 (5th July 2013) - Thammavongsy, Zachary; LeDoux, Micah E.; Breuhaus‐Alvarez, Andrew G.; Seda, Takele; Zakharov, Lev N.; Gilbertson, John D.
Abstract: A series of asymmetric iron(II) dichloride and dicarbonyl pyridinediimine (PDI) complexes that contain either pendant Lewis bases or Lewis acids located in the secondary coordination sphere were synthesized. These complexes are important intermediates in the reduction scheme of the small molecule CO2 on iron(II). The electrochemistry of the direduced FePDI(CO)2 complexes was evaluated for the 2‐electron oxidation from the reduced‐ligand to the neutral‐ligand species. The complexes with either pendant Lewis bases or Lewis acids located in the secondary coordination sphere displayed reduction potentials for CO release that span over 300 mV. Abstract : A series of direduced‐dicarbonyl iron pyridinediimine complexes containing either pendant Lewis bases or Lewis acids in the secondary coordination sphere were synthesized and examined for the electrochemical release of CO.